Which antiretroviral regimen is associated with higher adherence in Brazil? A comparison of single, multi, and dolutegravir-based regimens - Tarsilla Spezialli Cardoso; Juliana de Oliveira Costa; Edna Afonso Reis; Micheline Rosa Silveira; Palmira de Fátima Bonolo; Simone Furtado dos Santos; Maria das Graças Braga Ceccato
Abstract: We evaluated adherence to highly active antiretroviral therapy (HAART) and its associated factors according to the type of regimen in patients initiating treatment in Belo Horizonte, Minas Gerais State, Brazil. We measured adherence using the eight items Morisky Therapeutic Adhesion Scale (MMAS-8) and compared the use of "backbone" tenofovir/lamivudine plus efavirenz one tablet once-daily (STR) or dolutegravir in multi-tablet once-daily (MTR-DTG), or other multi-tablet regimens (MTR-other). We conducted a multivariate logistic regression analysis to address factors associated with adherence. A total of 393 patients were included, 254 used STR, 106 MTR-DTG, and 33 MTR-other. The overall adhesion rate was 44.8% (95%CI: 39.4; 50.1), 50% for MTR-DTG, 43.3% for STR and 39.4% for MTR-other. Multivariate analysis showed a higher chance of adherence among patients using MTR-DTG, those who received and understood counseling about their treatment and with a higher quality of life. Prior use of illicit drugs in the lifetime was associated with poorer adherence. Overall adherence was low, highlighting the need for strategies focusing on counseling about medicines and substance use. Pill burden was not an issue for patients using MTR-DTG once-daily, who achieved better results.